2016
DOI: 10.1111/gwat.12482
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of Coliform Bacteria Detection Rates in New Jersey Domestic Wells

Abstract: It is important that indicators of fecal pollution are reliable. Coliform bacteria are a commonly used indicator of fecal pollution. As other investigators have reported elsewhere, we observed a seasonal pattern of coliform bacteria detections in domestic wells in New Jersey. Examination of a statewide database of 10 years of water quality data from 93,447 samples, from 78,207 wells, generated during real estate transactions, revealed that coliform bacteria were detected in a higher proportion of wells during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 74 publications
2
11
0
Order By: Relevance
“…Work by Hynds et al () and Howard et al () lend support to infiltration use patterns as risk factors. Our earlier findings of seasonality as a risk factor (Atherholt et al ) further supports this theory.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Work by Hynds et al () and Howard et al () lend support to infiltration use patterns as risk factors. Our earlier findings of seasonality as a risk factor (Atherholt et al ) further supports this theory.…”
Section: Discussionsupporting
confidence: 83%
“…The second phase examined the influence of the timing and amount of precipitation on coliform detection rates in groundwater by exploring the relationship between cumulative precipitation over a series of days (1–30) prior to sampling of wells and the rates of coliform occurrences. This question arose from a previous study which revealed that a small seasonal difference in the total amount of precipitation, based on NJ monitoring station data, may have marginally contributed to the observed seasonal difference in coliform detection rates in domestic wells in New Jersey (Atherholt et al ). The third phase evaluated the likelihood of coliform occurrences given the effect of precipitation and other factors for which data were available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are abundant in the faeces of warm-blooded animals, including humans, and their presence indicates whether faecal contamination is present and whether potential risks from these and other pathogenic bacteria or viral agents may exist [10]. These bacteria have been used in many research studies for assessing microbial quality of water [11][12][13][14][15]. The study aims to i) evaluate the microbiological water quality of these dam waters and ii) determine the spatial distribution and the temporal variation E. coli and IE abundances in these reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…Transportation of coliform bacteria from surface and subsurface sources is dependent on various factors like the specific hydrogeological settings, depth of tube well, tube well construction, and the amount and intensity of precipitation (Atherholt et al, 2017). Shallow groundwater is more vulnerable than the deeper one because of the shorter vertical distance and the attenuation of pathogenic bacteria depends on retention and die-off in the flow path (van Geen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%